Egyptian shipyard partial lean manufacturing implementation - Mahmoud H. Kheireldin; Ibrahim S. Seediek; Mohamed M. Elgouhary (Maritime Research and Technology)
This study tries to define the notion of lean manufacturing as an engineering management strategy that can be used by Egyptian shipyards to assist them to compete in this global shipbuilding market. lean manufacturing uses tools like just-in-time, one-piece flow, and takt time, to improve product cycle times and quality by getting rid of waste in the manufacturing process. These techniques are the foundation for eliminating waste in the shipbuilding industry. To help Egyptian shipyards to get a decision regarding how to respond to lean shipbuilding, this study gave a thorough overview of the potential applications of Lean Manufacturing Principles. Additionally improved the presentation of lean manufacturing in a manner suitable for Egyptian culture, bringing the Egyptian shipbuilding sector closer to the principles of lean manufacturing. One of the lean manufacturing tools has been used as an example in a block assembly line at an Egyptian shipyard. the shipbuilding cycle time for a 125-ton block assembly has been reduced from 60 days to 30 days as the shops are capable to deliver two blocks in the same 60 days instead of 120 days, and the block production lead time was reduced to 50% of the original, reduction in the production lead time of block per man/hour to become 7100 instead of 9499. man/hour.   Received: 26 March 2023 Accepted: 01 May 2023 Published: 06 June 2023